Paranoid Schizophrenia With Type 2 Diabetes Mellitus And Chronic Suppurative Otitis Media: A Case Report - Muhammad Rizky Huryamin H; I Nyoman Ardi Widiatmika; Dewi Gotama; Devyntya Monica Putri; Afiyf Kaysa Waafi; Anak Agung Ngurah Bagus Adhitya Wirakusuma; Made Bayu Sanjaya Sanjaya (LPPM Universitas Dhyana Pura, 2026)
Schizophrenia is a chronic psychiatric disorder characterized by disturbances in thought processes, perception, emotion, and behavior and is frequently accompanied by medical comorbidities. This case report aimed to describe the clinical manifestations and management of paranoid schizophrenia accompanied by type 2 diabetes mellitus and chronic suppurative otitis media. A descriptive case-report method was applied to a 37-year-old woman. Data were collected through history taking, mental status examination, physical examination, supporting investigations, and review of medical records. Clinical assessment revealed findings consistent with paranoid schizophrenia, accompanied by type 2 diabetes mellitus and chronic suppurative otitis media. These comorbidities increased the complexity of the patient’s condition, requiring comprehensive evaluation of psychiatric symptoms, metabolic control, chronic ear infection, treatment adherence, and potential adverse effects of antipsychotic medication. The patient was managed using an integrated approach involving psychiatric treatment and appropriate management of the accompanying medical conditions. This case highlights the importance of multidisciplinary care, regular clinical monitoring, and continuity of treatment to achieve optimal outcomes in patients with schizophrenia and multiple medical comorbidities.